Precision frequency transfer with fiber frequency combs - Fermann, Martin E.; Lee, Kevin F.; Li, Peng; Rolland, Antoine; Jiang, Jie (Frontiers in Physics, 2022)
We review methods for precision transfer of frequencies across broad optical wavelength ranges. Single-branch supercontinuum generation allows for a frequency transfer stability of < 1×10-17 in 1 second across an octave. With supercontinuum stitching, highly coherent supercontinuum spectra spanning across more than two octaves are generated. With noise cancellation techniques a relative frequency transfer stability of  2×10-18 in 1 second can be achieved. Highly stable frequency transfer along with a maximization of power per mode at multiple freely selectable frequency bands is further enabled via pulse shaping techniques. We also include a brief review of general fiber combs and research aimed at frequency extension of frequency combs covering the whole spectral range from the XUV to the mid IR, power scaling of frequency combs as well as low noise microwave and mmwave technology enabled with frequency combs.